Motivasi Karyawan Brand Kaset Rusak Bersaing Dalam Dunia Clothing - Andrian Mayoreta; Krisna Agustian; Santi Pratiwi Hari Sandi; Dwy Epty Hidayati (Journal of Management and Social Sciences, 2023)
This observation aims to explain the performance of employees of a Cloting Brand clothing store in the Karawang area, namely (KASET RUSAK) whose address is Beside Mall Ramayana, jl. Tuparev No. 298, Nagasari, West Karawang sub-district, Karawang district, West Java province, postal code 41314. The contents of the explanation that will be explained about the MSME sector in the fashion sector concern the motivation of employees to compete in attracting public interest, especially young people, in buying clothes such as clothes, trousers, bags, shoes, bracelets and other souvenirs. This observation also explains the profile or history of the company, employee strategies and employee activities, prices and the number of products applied by the company, how the company survived and faced the effects of Covid-19 in the past 2 years. The process of data collection and observation was carried out using interview and observation methods within 1 to 2 days, to be precise on March 25s/d26 2023. This data collection technique obtains information related to the experience of company owners where the results of observations and interviews show that there is an interest or trend The highest rate for people who buy new clothes is in the month of Ramadan or before Eid al-Fitr.